Effect of sedated colonoscopy with different cost coverage on improving compliance with colorectal cancer screening in China - Zhuo, Lin; Kong, Yunxin; Chen, Siting; Ma, Yue; Cai, Ting; Pan, Jianqiang; Wang, Xiuying; Gao, Yihuan; Lu, Hang; Li, Xinyue; Zhao, Hongying; Mackay, Louisa; et al. (Frontiers in Oncology, 2023)
Background: Colorectal cancer is the third most common cancer in the world. Colonoscopy is the gold standard for colorectal cancer screening. However, the colonoscopy participation rate in China is much lower than in Europe and the United States. Since only non-sedated colonoscopies are offered in colorectal cancer screening program in China, the absence of sedation may contribute to the gap. Methods: To explore the effect of free and partially participant-paid sedated colonoscopy on improving colorectal screening participation, we conducted a cross-sectional study under the framework of the Cancer Screening Program in Urban China in Xuzhou from May 2017 to December 2020. Quanshan district was set as the control group and provided free non-sedated colonoscopy, Yunlong district was set as partially cost coverage group and offered partially participant-paid sedated colonoscopy, Gulou district was set as full cost coverage group and offered free sedation colonoscopies. Multivariate logistic regression was used for multivariate analysis of colonoscopy participation rates and colorectal lesion detection rate between groups. Results: From May 2017 to May 2020, 81,358 participants were recruited and completed questionnaire, 7,868 subjects who met high-risk conditions for CRC were invited to undergo colonoscopy. The colonoscopy participation rate of control group, partially cost coverage group, and full cost coverage group were 17.33% (594/3,428), 25.66% (542/2,112) and 34.41% (801/2,328), respectively. Subjects in the partially and the full cost coverage group had 1.66-fold (95%CI: 1.48-1.86) and 2.49-fold (95%CI: 2.23-2.76) increased rates compared with those in the control group. The adjusted PARs for the the partially and the full cost coverage group was 9.08 (95%CI: 6.88-11.28) and 18.97 (95%CI: 16.51-21.42), respectively. The detection rates of CAN in control group, partial cost coverage group and full cost coverage group were 3.54% (21/594), 2.95% (16/542) and 5.12% (41/801), respectively. There was no significant difference in the detection rate of each group. But sedated colonoscopy increased the cost. Conclusions: Sedated colonoscopy increased colonoscopy participation rates in both partial and full cost covered group. The partial cost coverage strategy may be a good way to increase colorectal cancer participation rates and quickly establish a colorectal cancer screening strategy in underfunded areas.